O programa de extensão universitária Proext no contexto das políticas educacionais no período de 2003 a 2012 : uma análise a partir da experiência da Universidade Federal de Uberlândia - Rodrigues, Valéria Maria (2014)
This research has as a survey object the University Extension Program -Proext (in Portuguese), in the context of the university education\'s policiesand its implication in the university extension inside Federal University of Uberlandia -UFU. It is situated in the State, Policiesand Education Management of the Pos-Graduated Program of Education College -Faced (in Portuguese). Has as general subject situate the Proext within the educational policiesfor the superior education, in context of the transformations in the role and significance of the university actually, and its developments at UFU between 2003 and 2012. Oriented by some particular objectives, will try to analyze the educational policies between 2003 and 2012 in the scenery of Brazilian society in such a way to understand its articulation with the transformations at the university and, more specifically, at UFU, in this period; situate a discussion around the university extension in context of The Pro-Rector Extension Forum of Brazilian Public Universities -Forproex ( in Portuguese), in such a way to capture its implications at the university extension policy and in scope of UFU; understand the Proext in the context of the discuss and the extension policies in Brazil and its implications at UFU. Methodologicallyit is situated in the spectrum of the qualitative research and sought to the content analyses through the documental research. The maindocumental sources were the law about university extension in Brazil, specially related to Proext, and the documents produced by Forproex. Throughout this studywe discussed about the meaning and outline that the university hasaccepted in its historical development and the educational policies that has been implanted of the superior education ambit in general and of the university extension specifically. Rescue the discuss and some experiences in the field of university extension at public university and, in this analysis movement, discuss the directions, ways and outlinesthat the university extension has been accepting in these universities. Recover, also, the contribution of Forproext in this discussion of making proposals to providing the extension policies and between them, are highlighted the Rondon Project , the Literacy Program of Brazil, the Provide Extension Funds Program and the Proext, the main subject of this search.In this analysis movement , UFU is situated in such way to evidence the implications, in this institution, of the policies and debates which are developed in the university extension field. At the end it was possible to show that in context of the educational policies and implemented policies at UFU the university extension is still sidelined, there aren´t more consistent actions around it. In this sense , was possible to demarcate some values as the nextricable connection betweeneducation -research -extension and the extension while a channel, not only of the production, but also of diffusion and exchange of knowledge, already reiteratedin the formulations about university extension, however it isn\'t yet consolidated in practices and in extension policies. We demonstrated also, that the Proext has been constituted in a important strategy of foment to the extension actions, but at the same time, it contributes with the limitation of the university in acting in its ambit once that it is made, essentially, at the unique funding source to university extension in the public institutions of Brazil superior study, what gave checkmate the autonomy of these institutions.